Pelatihan Penyusunan Micro-module Sebagai Upaya Peningkatan Kompetensi Guru MGMP Kimia Kabupaten Pangkep - Jusniar; Ashari, Ayu; Hastuti Agussalim (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Community service activities in the form of training in preparation of micro-modules This training was conducted to improve the competence of MGMP Chemistry teachers in Pangkep Regency in designing innovative, systematic, and curriculum-aligned teaching materials, thereby supporting conceptual understanding and student engagement. The training was conducted in three stages: the preparation stage, participant data collection, and the evaluation stage. booklet creation guide micro-module, the implementation stage, which includes the presentation of material, direct practice of makingmicro-moduleThe group and evaluation stages used a teacher competency questionnaire with a Likert scale of 1-5. Furthermore, data analysis used descriptive statistics to assess teacher competency. The activity was attended by 25 Chemistry teachers from various schools in Pangkep Regency and demonstrated an overall increase in teacher competency, providing benefits in the form of improved technical skills, pedagogical creativity, and readiness for implementation. micro-module in class and motivation to take further training. The conclusion is that the training on compiling micro-modules improves overall teacher competency, encourages the development of innovative teaching materials, and strengthens teachers' active involvement in learning, so continuous training is highly recommended to strengthen pedagogical skills and adaptation to 21st-century education